Characterization and expression profile of transient receptor potential channels in sea cucumber Apostichopus japonicus - Wang, Xuemin; Wang, Yixin; Wang, Yanlin; Storey, Kenneth B.; Chen, Muyan (Frontiers in Marine Science, 2023)
Apostichopus japonicus, as a representative temperate species of echinoderms, is highly sensitive to its complex and changeable marine environment. However, the molecular mechanisms by which A. japonicus perceives signals from such a diverse environment remain unclear. TRP (transient receptor potential) channels are well-known molecular sensors and are involved in the sensory system that allows these animals to perceive external environmental signals. In this study, we identified and characterized the AjTRPs and investigated their expression profiles in different tissues and in response to different heat stress treatments. A total of 54 TRPs were identified in A. japonicus. Gene structure analysis showed that the exon numbers and the domains of AjTRPs varied greatly. Phylogenetic analysis indicated that all AjTPRs were mainly grouped into six subfamilies including TRPA, TRPM, TRPC, TRPV, TRPML and TRPP. Copy numbers of each TRP member in marine invertebrates including A. japonicus were larger than in vertebrates, however some TRP channel members were lost. Expression profile detection suggested that the representative 15 AjTRP genes belonging to 6 subfamilies were expressed in all tissues examined and that TRPM2-1, TRPM2-2, TRPM3 and TRPC3-1 are potential thermo-TRP proteins involved in thermal regulation in A. japonicus. These results enrich the knowledge of TRP mediated sensory systems in echinoderms and provide theoretical support for clarifying the mechanism of aestivation of A. japonicus.